Determinan Kejadian Ruptur Perineum Pada Persalinan Pervaginam - Katili, Rusli A; Nurdin, St. Surya Indah; Ahmad, Zul Fikar (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Perineal rupture is a common complication of vaginal delivery and may result in both short-term and long-term adverse outcomes for women. This study aimed to analyze the determinants of perineal rupture among women undergoing vaginal delivery at Sitti Khadijah Hospital, Gorontalo. A retrospective cohort design was employed using secondary data obtained from medical records of women who delivered vaginally. A total of 205 women were included in the study. The inclusion criteria comprised women who had vaginal delivery, singleton pregnancy with cephalic presentation, and complete medical records according to the study variables. Determinants were assessed using logistic regression analysis. The multivariate analysis revealed that birth weight was the only variable significantly associated with the occurrence of perineal rupture (OR = 1.003; p = 0.023). In contrast, maternal age, employment status, parity, gestational age at delivery, interpregnancy interval, and duration of the second stage of labor were not significantly associated with perineal rupture. Birth weight was identified as the main determinant of perineal rupture in vaginal delivery at Sitti Khadijah Hospital, Gorontalo. Preventive efforts should therefore focus on early identification of pregnancies at risk of delivering large infants and the optimization of safe, evidence-based intrapartum care practices.